The safety and efficacy of sequential intramuscular/oral ziprasidone treatment of acute episode in patients with schizophrenia: a multicenter, open-labeled study - Yaxue Wu; Yanli Li; Weiye Liang; Luyuan Bai; Jianjin Yu; Keqing Li; Yunshu Zhang; Yanmei Guo; Zenglong Liu; Jian Wang; Congpei Zhang; Xijin Wang; et al. (BMC Psychiatry, 2023)
Abstract Background Ziprasidone mesylate injection is an atypical antipsychotic drug which is recently approved in China. In combination with its oral formulation, sequential therapy with ziprasidone brings new interventions to patients with agitation in the acute phase of schizophrenia. The purpose of this 7-day multicenter study conducted in China was to evaluate the efficacy and safety of ziprasidone sequential treatment through intramuscular/oral routes in agitated patients with schizophrenia. Methods A total of 95 patients were enrolled from three centers in this study. The study duration was 7 days. In the first 3 days, subjects were administered an intramuscular injection of ziprasidone 10–40 mg daily and started sequentially with oral ziprasidone 40–80 mg at dinner (or lunch) from the day of the last intramuscular injection. In the following 4 days, according to the severity of the symptoms and the drug response, 120–160 mg of ziprasidone was orally administered daily. In total, six visits were scheduled to assess the Positive and Negative Syndrome Scale (PANSS), the Behavioral Activity Rating Scale (BARS), the Clinical Global Impression of Severity (CGI-S), and Improvement (CGI-I) scores throughout the procedure. Lastly, adverse events were recorded during treatment. Results Out of the 95 patients that were enrolled, 83 cases were effectively completed. Visits 3, 4, 6, PANSS, and PANSS-excited component (PANSS-EC) subscale points, and Visit 2–Visit 6 viewpoints, BARS scale points, and baseline scores denote a progressive downward trend (P < 0.001). In this study, 62 adverse events were reported. The most common adverse events were extrapyramidal symptoms (EPS) (23 cases) and excessive sedation(10 cases), and 13 cases of prolonged QTc interval were reported. Conclusions Ziprasidone IM demonstrated significant and rapid reduction in agitation, and sequential oral formulation keep stability and continuation of the treatment can further ensure efficacy. Ziprasidone sequential therapy may provide a new approach to acute agitation in schizophrenic patients. Trial registration The Chinese Clinical Trials Registry; URL: https://www.chictr.org.cn : ChiCTR-OIC-16007970.